2017
DOI: 10.3168/jds.2016-12079
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effect of dietary intake of chromium propionate on the response of monocyte-derived macrophages from Holstein cows in mid lactation

Abstract: Chromium (Cr) has been reported to enhance immune function and improve insulin sensitivity and performance in beef and dairy cattle. However, its effect on bovine macrophage inflammatory and metabolic response is unknown. The objective of this study was to characterize the effect of dietary Cr on the inflammatory and metabolic response of polarized macrophages ex vivo. Twelve primiparous and 16 multiparous healthy Holstein cows in mid lactation (143 ± 37 d in milk) were enrolled in this study. Cows were fed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Different research groups have frequently observed the complete or partial failure of macrophages in producing NO − in cultures containing fetal bovine serum (FBS). The MDM from humans, cattle, sheep, goats, badgers, and ferrets in a culture containing FBS were found to be unable to produce a detectable level of NO − or approximately 20-to 50-fold less than macrophages from chickens (Denis, 1994;Dumarey et al, 1994;Arias et al, 1997;Ohki et al, 1999;Sacco et al, 2006;Zelnickova et al, 2008;Khalifeh et al, 2009;Guimarães et al, 2011;Azevedo et al, 2016;Bilham et al, 2017;Garcia et al, 2017). The FBS contains a considerable amount of immuno-regulatory cytokines and bioactive molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Different research groups have frequently observed the complete or partial failure of macrophages in producing NO − in cultures containing fetal bovine serum (FBS). The MDM from humans, cattle, sheep, goats, badgers, and ferrets in a culture containing FBS were found to be unable to produce a detectable level of NO − or approximately 20-to 50-fold less than macrophages from chickens (Denis, 1994;Dumarey et al, 1994;Arias et al, 1997;Ohki et al, 1999;Sacco et al, 2006;Zelnickova et al, 2008;Khalifeh et al, 2009;Guimarães et al, 2011;Azevedo et al, 2016;Bilham et al, 2017;Garcia et al, 2017). The FBS contains a considerable amount of immuno-regulatory cytokines and bioactive molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The cell isolation procedure was performed as described elsewhere ( 24 , 25 ) with minor modifications for isolation of different cell types. Briefly, diluted blood (2× with 2 mM EDTA in phosphate-buffered saline) underwent a differential gradient centrifugation step using Ficoll-paque PLUS (GE Healthcare, Pittsburgh, PA).…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, the rapid attraction of neutrophils contributes to the elimination of bacteria (Brodzki et al., 2014; Sheldon et al., 2014). In addition, the MΦs are attracted following neutrophils and are not only involved in bacterial elimination but also the secretion of antimicrobial peptides, the orchestration of inflammation, the activation of other immune cells (T‐ and B‐cells) and tissue repair (Dadarwal et al., 2017; Fischer et al., 2010; Garcia et al., 2017; Kauma, 2000; Sheldon et al., 2014).…”
Section: Introductionmentioning
confidence: 99%